The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jpy.12855
|View full text |Cite
|
Sign up to set email alerts
|

The physiological response of marine diatoms to ocean acidification: differential roles of seawater pCO2 and pH

Abstract: Although increasing the pCO2 for diatoms will presumably down‐regulate the CO2‐concentrating mechanism (CCM) to save energy for growth, different species have been reported to respond differently to ocean acidification (OA). To better understand their growth responses to OA, we acclimated the diatoms Thalassiosira pseudonana, Phaeodactylum tricornutum, and Chaetoceros muelleri to ambient (pCO2 400 μatm, pH 8.1), carbonated (pCO2 800 μatm, pH 8.1), acidified (pCO2 400 μatm, pH 7.8), and OA (pCO2 800 μatm, pH 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
4
24
0
Order By: Relevance
“…Decreases in respiratory metabolism may synergise with the increased rate of C uptake due to increased photosynthesis, promote increased growth rates, and explain the greatly boosted abundance in our site with increasing pCO 2 levels. Although species-specific responses are likely for diatoms, some generalisations have been suggested, for example, diatoms with lower CCM efficiencies are more likely to show a pronounced response [57], and larger centric diatoms are more likely to profit relative to smaller species [11,12]. This body of work aligns with our novel observations of the effects of ocean acidification on B. biddulphiana.…”
Section: Resultssupporting
confidence: 83%
“…Decreases in respiratory metabolism may synergise with the increased rate of C uptake due to increased photosynthesis, promote increased growth rates, and explain the greatly boosted abundance in our site with increasing pCO 2 levels. Although species-specific responses are likely for diatoms, some generalisations have been suggested, for example, diatoms with lower CCM efficiencies are more likely to show a pronounced response [57], and larger centric diatoms are more likely to profit relative to smaller species [11,12]. This body of work aligns with our novel observations of the effects of ocean acidification on B. biddulphiana.…”
Section: Resultssupporting
confidence: 83%
“…Elevated environmental CO 2 concentrations may facilitate carbon fixation by phytoplankton, as suggested by several studies of algal cells (Wu et al, 2010;Shi et al, 2019), including the present study. Thus, it is generally expected that increased seawater CO 2 concentrations will enhance marine primary productivity.…”
Section: Roles Of Eps Released By Diatoms In Response To Environmentasupporting
confidence: 68%
“…Thus, the possible biological consequences of elevated pCO 2 levels has recently received extensive research attention. In particular, several studies have reported the effects of elevated pCO 2 levels on diatoms at the physiological and ecological scales (Wu et al, 2010;Gao and Campbell, 2014;Shi et al, 2019). However, few studies have evaluated the molecular mechanisms underlying diatom responses to elevated pCO 2 levels.…”
Section: Introductionmentioning
confidence: 99%
“…Under OA conditions, the coastal diatom Thalassiosira weissflogii shows a faster particulate carbon production rate, whereas a pelagic species, Thalassiosira oceanica, grows slower, implying that under diel pH fluctuations the large coastal diatom appears to be more tolerant of the pH decline (Li et al, 2016). While there are species-specific responses to OA, diatoms with lower CCM efficiencies showed more pronounced responses to OA in terms of growth rate (Shi et al, 2019).…”
Section: Ocean Acidificationmentioning
confidence: 97%